Self-reported occupational hazards among waste management staff in Lalitpur Metropolitan City: A pilot study from Nepal - Pradhan, Abhipsa; Thapa, Anjana; Karki, Rajesh; Kaphle, Maheshor (International Journal of Occupational Safety and Health, 2025)
Introduction: Solid waste management is a major environmental and public health concern in Nepal. Workers face occupational health and safety concerns due to the materials they handle, the emissions from those materials, and the equipment they use. This study aimed to study the health status and occupational hazards existing among municipal waste collectors. Methods: A cross-sectional study was conducted among 125 municipal waste collectors working in Lalitpur Metropolitan City. Three organizations were selected randomly by using simple random sampling and the census method was applied to interview the respondents. Data entry was done in Epi Info 7, and analysis was in the SPSS 23 version. The chi-square test was used to measure the strength of the association. Results: Majority of respondents 99(95.2%) faced physical hazard, 65(62.5%) biological hazards. Likewise, 69(55.2%) had knowledge of its health effects, and 106(84.8%) had knowledge of occupational hazards. Nearly one-third 38(30.4%) used personal protective equipment (PPE) and 55(44%) had been vaccinated for tetanus. The health check-up in the past year of respondents was low 49(39.2%). A statistically significant association was found between the job category and the presence of physical, chemical, and biological hazards (p=0.041, 0.003, and 0.001 respectively). Conclusion: The study highlights inadequate utilization of PPE among respondents, particularly concerning given their strenuous work. While most workers had good mental health, more than half showed poor physical health. The study recommends organizations actively promote PPE use, administer tetanus and hepatitis vaccinations, and provide workplace training.